A New Countermeasure against Brute-Force Attacks That Use High Performance Computers for Big Data Analysis - Hyun-Ju Jo; Ji Won Yoon (International Journal of Distributed Sensor Networks)
Using high performance parallel and distributed computing systems, we can collect, generate, handle, and transmit ever-increasing amounts of data. However, these technical advancements also allow malicious individuals to obtain high computational power to attack cryptosystems. Traditional cryptosystem countermeasures have been somewhat passive in response to this change, because they simply increase computational costs by increasing key lengths. Cryptosystems that use the conventional countermeasures cannot preserve secrecy against various cryptanalysis approaches, including side channel analysis and brute-force attacks. Therefore, two new countermeasures have recently been introduced to address this problem: honey encryption and the structural code scheme. Both methods look different; however, they have similar security goals and they both feature distribution transforming encoders based on statistical schemes. We unify them into a statistical code scheme in this study. After explaining the statistical code scheme, we describe the structural code scheme, which has not been adopted as widely as the honey encryption.